Clinical Characteristics, Course, and Outcomes of Postpartum Vertebral Artery Dissections. (16th November 2020) - Azad, Hooman; Prasad, Nikil; Mitra, Akash; Shlobin, Nathan A; Hopkins, Benjamin; Cloney, Michael; Dahdaleh, Nader S
Abstract: INTRODUCTION: Vertebral artery dissections (VADs) in the postpartum period are rare, but can cause severe injury and death in otherwise healthy patients. There are only 13 reported isolated postpartum VADs (ppVADs) in the literature; this study adds 12 patients with 17 ppVADs. METHODS: Demographic and clinical data on consecutive patients treated at our institution were collected. The modified Rankin Scale (mRS) was used as a metric of neurologic status. ppVADs are presented as a 12-patient case series. Additionally, parametric data on ppVADs and the general cohort are compared, using Wilcoxon rank-sum tests. Univariate and multivariate regressions determine what factors are associated with neurologic improvement. RESULTS: Of 310 patients with 366 VADs during our study period, there were 12 patients with 17 ppVADs. These occurred 11.27 days (95% CI, -0.85, 23.39) after delivery with diagnosis 21.83 days (95% CI, 9.07, 34.61) after delivery. Five (42%) patients had a hypertensive disorder of pregnancy, and 4 (33%) had a history of migraine headaches. All ppVADs had headaches or neck pain as a presenting symptom. There were 3 (25%) associated ischemic strokes and 1 (8%) subarachnoid hemorrhage. Two (17%) had unfavorable mRS (2-6) at hospital discharge. Patients with ppVADs were younger (33.83 years v. 44.32 years, P = .018) and had a lower Charlson Comorbidity Index (CCI = 0 v. CCI = 0.99, P = .0038) than the general cohort. Their VADs more often were bilateral (42% v. 17%, P = .03) and had an associated pseudoaneurysm (50% v. 18%, P = .0068). Use of anticoagulant treatment was similar. In a multivariate analysis, factors predictive of change in mRS over the course of clinical follow-up were CCI (OR = 1.09, 95% CI, 1.02, 1.15), stroke (OR = 0.78, 95% CI, 0.65, 0.95), and mRS at hospital discharge (OR = 0.80, 95% CI, 0.74, 0.87). CONCLUSION: We report the largest cohort of postpartum VADs in the literature. Postpartum VADs occur in younger, healthier patients than in the general cohort, raising questions about mechanism of injury, which has been hypothesized to be due to endocrine changes in pregnancy. Still, the majority of ppVADs have good neurologic outcomes.